Limited clinical significance of tissue calprotectin levels in bowel mucosa for the prediction of complicated course of the disease in children with ulcerative colitis - Fabian, Ondrej; Hradsky, Ondrej; Lerchova, Tereza; Mikus, Filip; Zamecnik, Josef; Bronsky, Jiri (Pathology, research and practice, 2019)
BACKGROUND: Fecal calprotectin (F-CPT) represents one of the most widely used biomarkers for intestinal inflammation. However, the levels may be false negative or false positive in some situations. AIMS: To evaluate the usefulness of immunohistochemical (IHC) detection of tissue calprotectin (T-CPT) in bowel mucosa in children with ulcerative colitis (UC). We focused at correlation of T-CPT with levels of F-CPT and endoscopic and microscopic disease activity at the time of diagnosis and tested whether T-CPT could serve as predictor of complicated course of the disease. METHODS: Forty-nine children with newly diagnosed UC between 6/2010-1/2018 entered the study. Endoscopic activity was objectified using the Ulcerative Colitis Endoscopic Index of Severity (UCEIS), clinical activity by Pediatric Ulcerative Colitis Activity Index (PUCAI) and microscopic activity by Geboes and Nancy score. The IHC staining for CPT antigen was performed on bioptic samples from 6 bowel segments and the number of CPT + cells were counted per 1HPF. During the minimal follow-up of 12 months we searched for presence of complications. As outcome for Cox regression model we used composite endpoints: A) Acute Severe Colitis, colectomy, anti-TNF treatment; B) systemic corticotherapy; C) systemic 5-aminosalicylic acid therapy. RESULTS: Neither levels of T-CPT nor values of UCEIS, Geboes or Nancy score predicted the given complications. We found F-CPT levels (HR 2.42 and 2.52) and PUCAI > 40 points (HR 2.98) as predictors of time to endpoints B and C. Good correlation was found between T-CPT levels and Geboes score (k = 0.65) and Nancy score (k = 0.62) and modest with F-CPT (k = 0.44), UCEIS (k = 0.38) and PUCAI (k = 0.42). CONCLUSIONS: T-CPT correlated well with microscopic scores. F-CPT and PUCAI appear to be better predictors of unfavorable outcome in patients with UC.
Keywords: Feces; ulcerózní kolitida; Reproducibility of Results; reprodukovatelnost výsledků; Outcome; Retrospective Studies; Colectomy; antiflogistika; Prognosis; Predictive Value of Tests; mladiství; imunohistochemie; věk při počátku nemoci; gastrointestinální látky; kolektomie; mužské pohlaví; prediktivní hodnota testů; Gastrointestinal Agents; Intestinal Mucosa; Leukocyte L1 Antigen Complex; dítě; Colonoscopy; leukocytární L1-antigenní komplex; Child; Colon; Immunohistochemistry; ženské pohlaví; prognóza; feces; retrospektivní studie; Anti-Inflammatory Agents; Humans; biologické markery; kolon; střevní sliznice; Age of Onset; Biomarkers; Ulcerative colitis; Female; Calprotectin; Adolescent; Colitis, Ulcerative; lidé; Male; kolonoskopie